EKSTRAKSI GELATIN DARI LIMBAH TULANG IKAN KAKAP MERAH (Lutjanus sp) DENGAN METODE ASAM - Rahmawati Saleh (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2011)
Red Snapper (Lutjanus sp) fish bone was product from red snapper fillet processing which had not been used optimal. The utilisation of fresh red snapper fishbone to produce gelatine has not been frequently performed. The research aimed to produce gelatine out of the red snapper fishbone waste and determine the best condition of pH and temperature for the extraction with acid method. The result showed that the soaking in citrid acid solution with pH 3, a seven day soaking period and a temperature 90oC were the best treatment condition of all. Under this condition gave 10,02% yield with viscosity 7 centipoises, pH 6,7 and gel strength 81,08 bloom, which fulfils the Tourtellote standard.